Pesquisa dos empreendimentos e empreendedores do centro comercial de Francisco Dantas - RN - Dantas, Júlio César (Universidade Federal Rural do Semi-Árido, 2018)
At the present moment, it is perceived that Brazil has a high growth in the entrepreneurship sector, which is of fundamental importance to the process of economic development of a society, since it drives growth motivating the use of new technologies, products and services. The present work had the objective of analyzing and characterizing the commercial and service enterprises of the city of Francisco Dantas, located in the State of Rio Grande do Norte, where this analysis will be carried out through the collection of data and information collected with the objective of obtaining a profile Of its ventures as well as of its entrepreneurs. After comparing the data from the survey carried out in the city of Francisco Dantas-RN with neighboring cities, this municipality and its region can be characterized in the state economic scenario. In the applied field survey, a questionnaire was used with objective questions that sought to analyze the age range, gender distribution in the labor market, educational level, type of enterprise, length of useful life of companies, among other characteristics.
Monografia
Keywords: Perfil empreendedor; Empreendedorismo; Cenário econômico; Francisco Dantas – RN; Profile of the entrepreneur; Entrepreneurship; Economic scenario; Francisco Dantas-RN; Development; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA